2009
DOI: 10.1186/1471-2431-9-21
|View full text |Cite
|
Sign up to set email alerts
|

Hyperbaric treatment for children with autism: a multicenter, randomized, double-blind, controlled trial

Abstract: Background: Several uncontrolled studies of hyperbaric treatment in children with autism have reported clinical improvements; however, this treatment has not been evaluated to date with a controlled study. We performed a multicenter, randomized, double-blind, controlled trial to assess the efficacy of hyperbaric treatment in children with autism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
91
1
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(95 citation statements)
references
References 71 publications
2
91
1
1
Order By: Relevance
“…They then published two case series suggesting improvement in ASD symptoms with HBO 2 T. 105,106 The only controlled trial of HBO 2 T in ASD was reported by the same team in 2009. 107 This was a multisite, randomized, double-blind trial of 62 well-characterized young children with ASD. Children were randomized to receive 40 onehour sessions over a 4-week period of either active treatment (24% oxygen at 1.3 atmospheres absolute [ATA]) or control treatment (21% oxygen at 1.03 ATA).…”
Section: Biologically Based Practicesmentioning
confidence: 99%
See 1 more Smart Citation
“…They then published two case series suggesting improvement in ASD symptoms with HBO 2 T. 105,106 The only controlled trial of HBO 2 T in ASD was reported by the same team in 2009. 107 This was a multisite, randomized, double-blind trial of 62 well-characterized young children with ASD. Children were randomized to receive 40 onehour sessions over a 4-week period of either active treatment (24% oxygen at 1.3 atmospheres absolute [ATA]) or control treatment (21% oxygen at 1.03 ATA).…”
Section: Biologically Based Practicesmentioning
confidence: 99%
“…The authors reported that children in the treatment group had significant improvements in overall functioning, receptive language, social interaction, eye contact, and sensory and cognitive awareness, compared with children who received slightly pressurized room air. 107 In response to this controversial report, the UHMS 108 published a position paper in 2009 outlining concerns of ascertainment bias, loss of data, author conflict of interest, and most fundamentally a concern that the very low oxygen and pressures used in the so-called treatment (24% O 2 and 1.3 ATA) do not actually constitute HBO 2 T. This position paper refutes the findings of the Rossignol team's 2009 RCT report, 107 stating that the purported positive findings were invalid interpretations of the data and that in fact, no significant differences were demonstrated between the control and treatment arms. The UHMS position paper goes on to point out that "one does not require a [hyperbaric] chamber to deliver this dose."…”
Section: Biologically Based Practicesmentioning
confidence: 99%
“…We are not aware of any studies that have examined changes in markers of oxidative stress in children with ASD undergoing HBOT. Two previous small, randomized, controlled trials of HBOT have been conducted in children with ASD, with one reporting improvements in overall symptoms (30% of children improved on the CGI-Improvement score in the HBOT group versus 8% in the placebo group), 52 and the other trial resulted in a finding of no effect. 53 Because one of the main postulated mechanisms for HBOT improving symptoms of autism is an anti-inflammatory effect, we conducted an open-label clinical trial in 10 children between the ages of 3 and 8 with ASD to determine if there were observable changes in detailed markers of inflammation after treatment.…”
Section: Inflammation: Hyperbaric Oxygen Therapymentioning
confidence: 99%
“…HBA in humans has already been applied in settings related to health, beauty, and sports. In medical settings, it has been used to treat disorders such as autism [2,[16][17][18], and cerebral palsy [4]. Therefore, we hypothesized that HBA would be more appropriate than HBO for use with small animals, although such application has not been reported to our knowledge.…”
mentioning
confidence: 99%
“…However, this protocol has been based on past experience rather than scientific experimentation, because few studies of HBA in humans have been reported [2,4,[16][17][18]. Thus, we sought to assess the safety of HBA and determine a protocol for it in dogs.…”
mentioning
confidence: 99%